Application of the C3 inhibitor compstatin in a human whole blood model designed for complement research – 20 years of experience and future perspectives. (January 2022) - Mollnes, Tom E.; Storm, Benjamin S.; Brekke, Ole L.; Nilsson, Per H.; Lambris, John D.
Abstract: The complex molecular and cellular biological systems that maintain host homeostasis undergo continuous crosstalk. Complement, a component of innate immunity, is one such system. Initially regarded as a system to protect the host from infection, complement has more recently been shown to have numerous other functions, including involvement in embryonic development, tissue modeling, and repair. Furthermore, the complement system plays a major role in the pathophysiology of many diseases. Through interactions with other plasma cascades, including hemostasis, complement activation leads to the broad host-protective response known as thromboinflammation. Most complement research has been limited to reductionistic models of purified components and cells and their interactions in vitro. However, to study the pathophysiology of complement-driven diseases, including the interaction between the complement system and other inflammatory systems, holistic models demonstrating only minimal interference with complement activity are needed. Here we describe two such models; whole blood anticoagulated with either the thrombin inhibitor lepirudin or the fibrin polymerization peptide blocker GPRP, both of which retain complement activity and preserve the ability of complement to be mutually reactive with other inflammatory systems. For instance, to examine the relative roles of C3 and C5 in complement activation, it is possible to compare the effects of the C3 inhibitor compstatin effects to those of inhibitors of C5 and C5aR1. We also discuss how complement is activated by both pathogen-associated molecular patterns, inducing infectious inflammation caused by organisms such as Gram-negative and Gram-positive bacteria, and by sterile damage-associated molecular patterns, including cholesterol crystals and artificial materials used in clinical medicine. When C3 is inhibited, it is important to determine the mechanism by which inflammation is attenuated, i.e., whether the attenuation derives directly from C3 activation products or via downstream activation of C5, since the mechanism involved may determine the appropriate choice of inhibitor under various conditions. With some exceptions, most inflammatory responses are dependent on C5 and C5aR1; one exception is venous air embolism, in which air bubbles enter the blood circulation and trigger a mainly C3-dependent thromboembolism, with the formation of an active C3 convertase, without a corresponding C5 activation. Under such conditions, an inhibitor of C3 is needed to attenuate the inflammation. Our holistic blood models will be useful for further studies of the inhibition of any complement target, not just C3 or C5. The focus here will be on targeting the critical complement component, activation product, or receptor that is important for the pathophysiology in a variety of disease conditions. Highlights: Investigating the role of complement in inflammation requires holistic models. Two effective whole blood models use lepirudin or GPRP as an anticoagulant. Complement crosstalk with other molecular and cellular systems can be investigated. Comparing C3- and C5-inhibition distinguish their respective role in inflammation. The data have consequences for future complement treatment in human diseases.